Vocal behavior of the elusive purple frog of India (Nasikabatrachus sahyadrensis), a fossorial species endemic to the Western Ghats. - Ashish Thomas (Public Library of Science (PLoS), 2014)
Quantitative descriptions of animal vocalizations can inform an understanding of their evolutionary functions, the mechanisms for their production and perception, and their potential utility in taxonomy, population monitoring, and conservation. The goal of this study was to provide the first acoustical and statistical analysis of the advertisement calls of Nasikabatrachus sahyadrensis. Commonly known as the Indian purple frog, N. sahyadrensis is an endangered species endemic to the Western Ghats of India. As the only known species in its family (Nasikabatrachidae), it has ancient evolutionary ties to frogs restricted to the Seychelles archipelago (Sooglossidae). The role of vocalizations in the behavior of this unique species poses interesting questions, as the animal is fossorial and potentially earless and it breeds explosively above the soil for only about two weeks a year. In this study, we quantified 19 acoustic properties of 208 calls recorded from 10 males. Vocalizations were organized into distinct call groups typically composed of two to six short (59 ms), pulsatile calls, each consisting of about five to seven pulses produced at a rate of about 106 pulses/s. The frequency content of the call consisted of a single dominant peak between 1200-1300 Hz and there was no frequency modulation. The patterns of variation within and among individuals were typical of those seen in other frogs. Few of the properties we measured were related to temperature, body size, or condition, though there was little variation in temperature. Field observations and recordings of captive individuals indicated that males engaged in both antiphonal calling and call overlap with nearby calling neighbors. We discuss our findings in relation to previous work on vocal behavior in other fossorial frogs and in sooglossid frogs.